Freud et les Berlinois. - Sokolowsky, Laura, author.
1 online resource.
Keywords: "Laura Sokolowsky's survey of psychoanalysis under Weimar and Nazism explores how the paradigm of a 'psychoanalysis for all' became untenable as the Nazis rose to power. Discussing the relations of psychoanalysis with politics and ethics, as well as the origin of the Lacanian movement as a response to the institutionalisation of psychoanalysis during the Nazi occupation, this book is fascinating reading for scholars and practitioners of psychoanalysis working today"--